A standardised Lithuanian version of Strenghts and Difficulties Questionnaire (SDQ) for school-aged children - Gintilienė, Gražina; Girdzijauskienė, Sigita; Černiauskaitė, Dovilė; Lesinskienė, Sigita; Povilaitis, Robertas; Pūras, Dainius (Psichologija, 2004)
Strengths and Difficulties Questionnaire (SDQ) developed by R. Goodman (1997) has been widely used in epidemiological studies throughout the world as a screening measure for mental health in children and adolescents. The SDQ comprises 25 items plus supplement on impact of the difficulties for the child and family. There are 5 subscales: Prosocial behaviour, Hyperactivity, Emotional symptoms, Conduct problems and Peers problems, the last four adding up to the Total Difficulties score. The design of the SDQ with both strength’ and difficulties’ items supposedly increases acceptability of the instrument on behalf of informants and make questionnaire especially suitable for studies of general population were the majority of children are healthy. Three SDQ versions (parent, teacher and self-report) were translated into Lithuanian language and psychometric properties of those Lithuanian SDQ versions are presented and analysed in this article. Representative sample of children aged 7–16 years (n = 2626) was randomly selected from 14 big town, 9 town and 20 country schools. 2447 parent versions, 2613 teacher versions and 1612 self-report versions were completed. SDQ self-report version was administered only to 11–16 year olds. Data analysis based on method of internal consistency, item inter- and intra-scale correlation, including exploratory and confirmatory factor analysis, comparison of data in clinical and non-clinical groups (62 children) and inter-rater correlations showed adequate psychometric properties of the Lithuanian SDQ. Cronbach’s alpha for the total difficulties score was in three informant reports 0.72–0.85, while the range in different subscales was 0.34–0.86. As raters, the teachers had the best internal consistency. The lowest level of alpha was in self-report version. Correlation analysis confirmed the postulated structure of the SDQ in all three versions, while the results of factor analysis had some exceptions to it. Lithuanian cut-off points were similar of those found in British sample. Applying Cohen’s criteria for the effect size between British and Lithuanian samples all the SDQ subscales felt in a low area except prosocial behaviour, emotional symptoms and total difficulties subscales in parents reports and prosocial subscale in self-report which felt in the moderate area. The present study gives further evidence of usefulness of the Lithuanian SDQ as screening instrument for research and clinical purposes.
Keywords: SDQ